Presupposition in Interrogative Headlines on “allkpop” News and Gossip Site - Rubiyanti, Afrin (LANTERN (Journal on English Language, Culture and Literature), 2013)
In Utterance, there are pre-assumptions that are unsaid but still communicated. Therefore, the writer has an interest in analyzing those pre-assumptions. To show those assumptions, the writer uses presupposition theory. The writer only focuses on questions texts. The writer uses interrogative headlines on “allkpop” news and gossip site from 20 – 26 February 2013 as the data. The writer uses purposive sampling method and non participant observation to get these data. The data are analyzed by presupposition triggers of questions. The purpose is to elaborate the presupposition in interrogative headlines. Moreover, after knowing the presupposition, the writer wants to show the indication of those presuppositions. The other purpose of this thesis is to elaborate the functions of those interrogative headlines based on the presupposition analysis. Based on the analyses, the presuppositions of interrogative texts indicate that there is a ‘case’. According to those analyses, interrogative headlines have some functions, that is representing the readers’ position, raising the readers’ curiosity, and lead the readers to the answer. Therefore, those headlines can increase the number of the readers, the popularity and the economy value of the news media.